The Role of Minority Stress in Psychological Distress and Hazardous Drinking Among Sexual Minority College Student Victims of Intimate Partner Violence - Edwards, Katie M. (Journal of interpersonal violence, 2024)
Sexual minority, individuals who are not heterosexual, college students experience high rates of intimate partner violence (IPV), which is linked to a myriad of deleterious outcomes. However, little work has evaluated whether there are differences in IPV outcomes among sexual minority college students as compared to heterosexual college students. Further, the extent to which minority stress at the institutional and individual level relates to IPV outcomes among sexual minority students is understudied. As such, the purpose of the current study was to evaluate IPV outcomes in a large sample of undergraduate students attending 18 medium- to large-sized universities across the contiguous U.S. Results supported that sexual minority victims of IPV had more anxious and depressive symptoms than heterosexual victims of IPV but were not more likely to engage in hazardous drinking. Further, analyses supported that several campus-level (but not individual-level) indicators of minority stress moderated the relation between IPV victimization and negative outcomes among sexual minority students, such that the association between IPV and negative outcomes was stronger among students embedded in campuses with higher levels of minority stressors. Results support the critical importance of interventions addressing campus-level minority stressors to reduce deleterious IPV outcomes among sexual minority college student victims.